Search for B+c → π+μ+μ− decays and measurement of the branching fraction ratio β(B+c → ψ(2S)π+)/β(B+c → J/ψπ+) - Aaij, Roel; Bachmann, Sebastian; Carus, Leon; Caspary, Rowina; Celani, Sara; Cocha Toapaxi, Carlos; De Cian, Michel; Esen, Sevda; Frau, Giulia; Glaser, Fabian; Günther, Paul André; Han, Xiaoxue; et al. (The European physical journal. C, Particles and fields, 2024)
The first search for nonresonant B+c → π+μ+μ− decays is reported. The analysis uses proton–proton collision data collected with the LHCb detector between 2011 and 2018, corresponding to an integrated luminosity of 9 fb−1 . No evidence for an excess of signal events over background is observed and an upper limit is set on the branching fraction ratio B(B+c → π+μ+μ−)/B(B+c → J/ψπ+) < 2.1×10−4 at 90% confidence level. Additionally, an updated measurement of the ratio of the B+c → ψ(2S)π+ and B+c → J/ψπ+ branching fractions is reported. The ratio B(B+c → ψ(2S)π+)/B(B+c → J/ψπ+) is measured to be 0.254 ± 0.018 ± 0.003 ± 0.005, where the first uncertainty is statistical, the second systematic, and the third is due to the uncertainties on the branching fractions of the leptonic J/ψ and ψ(2S) decays. This measurement is the most precise to date and is consistent with previous LHCb results.